Student and Teacher Perceptions of Features in an English Textbook for Junior High School - ., Senowarsito; ., Suwandi; ., Siti Musarokah; Nur Ardini, Sukma; Nimer Abdalqader Abu Jweid, Abdalhadi (KnE Social Sciences, 2022)
Textbooks have been found to have weaknesses, affecting the curriculum, approaches, methods, and teaching materials. Therefore, changes need to be made to achieve maximum learning outcomes. The objective of the study was to investigate the perception of teachers and students towards English teaching materials that followed a pragmatic perspective as a learning resource to build the communicative competence of junior high school students. Quantitative research with data collection using a 5-scale Linker questionnaire was used to measure the English for Junior High School Students: Pragmatics Based textbook. There were 9 teachers and 82 students who filled out 20 questions about their perceptions. The results showed that the teacher’s perceptions were: feasibility of content/material (61%), presentation in books (63%), language (59%) and dialogue content conformity (50%). Meanwhile, the student’s perception questions included adjustments to students’ abilities. These were the vocabulary used in the book, dialogues contained in the book, easy-to-understand instructions and exercises. The results showed that 50% of student respondents felt that the textbook was very appropriate. Hence, it can be concluded that the content of the English textbook with a pragmatic perspective was appropriate for seventh grade junior high school students in Semarang. Keywords: Textbooks, Pragmatics, Perceptions, Junior High School